Uncovering the metabolic capacities of H. pylori 26695 using 13C labeling experiments - Correia, Daniela M. (2015)
The determination of nutritional requirements of pathogenic organisms is of great significance for understanding host-pathogen interactions. Despite the knowledge obtained so far concerning amino acid requirements in H. pylori, it is still unclear which are the metabolic pathways used for biosynthesis and catabolism. Thus, information on the carbon flow in this organism is required. Glutamate is a very important metabolite in bacterial metabolism that can be used as a carbon and nitrogen source. 13C flux analysis has been largely applied to characterize phenotypes by quantifying in vivo the carbon fluxes. One of the most important applications of this approach is the identification of active pathways in less-studied organisms. Thus, in order to clarify the metabolic pathways used by H. pylori 26695, 13C labeling experiments with 13C-glutamate were conducted and labeled amino acids in biomass hydrolysates were analyzed by GC-MS. The obtained results confirmed L-glutamate as a potential sole and effective carbon source for H. pylori. Overall, all non-essential amino acids, except proline, presented a 13C labeling pattern. We hypothesized that L-proline is produced from L-arginine, while L-alanine is probably produced from pyruvate by alanine dehydrogenase. Additionally, the full usage of complete TCA cycle, under the conditions used, was also demonstrated.